Evaluación de la contaminación sonora en el distrito de la Esperanza, provincia de Trujillo durante el mes de marzo de 2019 - Azañedo Alva, Johanna Natali (2019)
Currently, economic and demographic growth in different regions of the world comes hand in hand with a growing environmental issue. Noise or noise pollution is one of the most prominent and worrisome in recent times, as it is present in all urban centers and directly impacts the health and quality of life of the population. The District of La Esperanza province of Trujillo is no stranger to this problem, which is why in the present investigation the level of noise in the entire district was evaluated and the results were compared with the current Peruvian Regulations, the Environmental Quality Standards of DS approved noise 085-2003-PCM. For the development of this research, the national environmental monitoring protocol was taken as a guide, 206 points resulting from the superposition on the plane of a 250m x 250m grid were selected. The monitoring was carried out from Monday to Sunday during the day and its results were processed in the Arc Gis software generating the noise map of the District of La Esperanza where it is evident that the areas most vulnerable to noise pollution are the avenues and streets of higher vehicular traffic, in addition to the results obtained for the commercial area, 11% exceed the environmental quality standards for noise, in a special area 67% exceeds regulations, being the area most vulnerable to the impacts caused by noise pollution, in the industrial zone 3% and in the residential area 48% is greater than the ECA-Noise. Based on the survey carried out during the month of March 2019 to 150 people from the District of La Esperanza, 89% of the respondents consider that noise affects the quality of life, 90% consider the noise caused by traffic annoying vehicular, 75% consider that noise is harmful and causes health diseases; However, 95% are not aware of the regulations regarding this problem